Empowering the Nigeria Health Care System through the Use of Artificial Intelligence (Lead City International Journal of Library, Information & Communication Sciences, 2025)
The study examined the use of AI in Nigeria healthcare towards providing effective and efficient services using a systematic scoping review method. The study adopted secondary information sources from the internet which include the use of journal articles, e-books, databases and websites of organizations, healthcare systems, news, and others. Information obtained was analyzed using thematic analysis and whence findings are presented. The findings of this study show that AI can revolutionize personalized medicine, optimize medication dosages, enhance population health management, provide virtual health assistants, support mental health care, improve patient education, and others which could enhance healthcare service provision and outcomes in the Nigeria healthcare system. AI in Nigeria healthcare system is just a recent innovation, and only few such as CareAi, ZMP Inc., and others have been successfully deployed to enhance healthcare service delivery in the Nigeria healthcare system. Also, despite the benefits accruing to AI in the Nigeria healthcare, several challenges such as data privacy and quality, ethical and legal issues, patient safety and accuracy, low internet connectivity, electricity, and hardware issues affect the successful implementation and use of AI in the Nigeria healthcare system. The study recommends that governments, policy makers and medical professionals should endeavour to provide sensitization information and other working mechanisms that enhance the propensity of the usefulness of AI towards ensuring a better healthcare provision in the Nigeria healthcare system.